ISSUES OF ENSURING STABILITY OF REVENUES OF LOCAL BUDGETS - Shoydaliyev Umid Eshquvat o'g'li (European Science Publishing, 2024)
Effective organization of local budget revenue formation policy in modern statehood plays an important role in solving the tasks of socio-economic development of regions. In the development of revenue policy, it is important to objectively assess the possibilities of regions for the mobilization of taxes and payments in the budget system, increase the effectiveness of factors affecting the mechanisms of formation of local budget revenues, and assess possible negative socio-economic consequences.